Automatic Weather Observation System - Mohamad Noor, Faris Effendy (IRC, 2020)
Weather forecast had always been important aspect to be considered in planning daily activity. For some industry, adverse weather can stop their business operation thus result in significant financial risk. Since the oil & gas is highly impact by adverse weather, PETRONAS GTS and Universiti Teknologi Petronas (UTP) are finding solution by designing and developing a prototype of Automatic Weather Observation System that can be used to assist in activity planning. The system aims with minimum cost and easy to handle features. The project research will be conducted using Visala WXT534 Weather Transmitter, Raspberry Pi 4 microprocessor and Phyton programming language to process information. This study will explain the whole process starting with the transducer record surrounding temperature, humidity & barometric pressure until the raw data is processed for data analysis. The data will be present in the form of graph as previous study shows using graphical image like graphs, charts and diagrams can assist user to acquire clearer picture of the research and help to compare with other data. The system will provide revolutionary & cost effective solution for the industry.